2017
DOI: 10.1016/j.mmcr.2017.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Disseminated phaeohyphomycosis in a dog

Abstract: Phaeohyphomycosis is a rare but emerging disease caused by dematiaceous fungi. Here we describe the case of an immunosuppressed dog with disseminated phaeohyphomycosis secondary to Bipolaris spicifera infection. Regionally extensive infiltration of the paw pads, skin, myocardium, liver, renal interstitium and diaphragm was identified on histopathology. Candida glabrata and Fusarium oxysporum were also cultured from multiple sites post-mortem. The dog was treated with fluconazole, itraconazole, terbinafine and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 18 publications
(25 reference statements)
0
9
0
Order By: Relevance
“…In dogs, Curvularia lunata, C. geniculata or C. spicifera (syn. Bipolaris spicifera ) cause cutaneous/subcutaneous, 11‐16 osseous 17 or abdominal 18 granulomas; corneal ulceration; 19,20 or disseminated systemic disease with cutaneous, cardiac and renal involvement 21,22 . CNS involvement of Curvularia spp.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In dogs, Curvularia lunata, C. geniculata or C. spicifera (syn. Bipolaris spicifera ) cause cutaneous/subcutaneous, 11‐16 osseous 17 or abdominal 18 granulomas; corneal ulceration; 19,20 or disseminated systemic disease with cutaneous, cardiac and renal involvement 21,22 . CNS involvement of Curvularia spp.…”
Section: Discussionmentioning
confidence: 99%
“…CNS involvement of Curvularia spp. has been reported in a dog with central vestibular signs and concurrent renal involvement, 23 whereas the fungus has been found in histopathological sections of the brain of a neurologically normal dog with cutaneous phaeohyphomycosis by Curvularia spicifera 22 . In cats, Curvularia lunata and C. spicifera (syn.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This species has been increasingly recognised as an opportunistic pathogen in people with the emergence of HIV infections and increasing use of immunosuppressive drugs 14 22. In dogs, C glabrata has been mostly involved in urinary tract infections although two cases of peritonitis3 23 and disseminated infection have also been reported 2 24…”
Section: Discussionmentioning
confidence: 99%
“…Candida albicans and some other Candida species have been identified in urinary tract infections in cats and dogs (Pressler et al 2003, Jin andLin 2005). It was reported that, Candida glabrata (together with Fusarium oxysporum) were isolated in a patient who started with foot soles and skin lesions and continued myocardial, liver, renal interstitium in dog (Rothenburg et al 2017). In addition, Candida albicans was isolated from samples of internal organs of sepsis foals with new born necrotizing enterocolitis, renal insufficiency and incompatibility syndrome.…”
Section: Introductionmentioning
confidence: 99%